Synchronized Agent Groups for Influencing Human's Movement, Synchronization, and Perception - Meneses Carnero, Alexis José (2022)
In this work, the influence of a group of robots on the synchronization between two humans was investigated. Furthermore, the influence of groups of agents on the movement of humans was investigated. Finally, the influence of a group of agents on the perception of feelings was investigated. It was concluded that groups of agents can improve synchronization, change the type of movement of humans, and improve positive emotions in interactions.